PROFESSIONAL AND AESTHETIC APPROACH TO TYPES OF WOMEN’S CLOTHING - Gaybullaeva, Yulduz (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article is devoted to the study of the professional and aesthetic approach to the types of women's clothing. The article provides information about clothing materials, picture and color combinations, tools and manuals, and professional parts used in the professional approach to women's clothing. And the aesthetic approach gives ideas about colors, silhouettes, design elements and materials to make the appearance of women's clothing exciting. The article emphasizes the importance of a professional and aesthetic approach in defining the personal expression and identity of women's clothing.